Using Index Card Match in Developing Vocabulary of the Eighth-Grade Students in Junior High School - Mulyani, Sri; Marhum, Mochtar; Hasna, Hasna; Agussatriana, Agussatriana (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Vocabulary forms the essential basis for students’ language proficiency, supporting their growth in reading, writing, speaking, and listening. A well-developed vocabulary not only improves comprehension but also enables effective communication in both oral and written contexts. This research aims to evaluate the impact of Index Card Match method on the vocabulary development of eighth-grade students of Sekolah Menengah Pertama (SMP) Negeri 9 Palu, highlighting the importance of vocabulary in English learning and the need for interactive and effective teaching methods to develop students’ vocabulary skills. A quasi-experimental design was employed, involving an experimental group taught using Index Card Match and a control group receiving conventional method. A sample of 64 students was selected through cluster random sampling from total population of 352 eighth-grade students, ensuring representativeness. This research utilized a set of 10 multiple choice questions and 10 matching items as instruments, which has been validated through evaluation and testing to ensure reliability. The findings indicated that the mean pre-test score for the experimental group was 47.81, compared to 49.22 for the control group. In contrast, the post-test mean score for the experimental group rose to 69.69, while the control group scored 42.03. The Mann-Whitney U test was employed due to the non-normal distribution of the data, revealing a significant difference between the two groups (p<0.05). In short, this indicates that the Index Card Match method positively impacts vocabulary development, accentuating its academic and pedagogical significance in improving students’ language skills.